False‐negative Interpretations of Cranial Computed Tomography in Aneurysmal Subarachnoid Hemorrhage. (17th April 2016) - Mark, Dustin G.; Sonne, D. Christian; Jun, Peter; Schwartz, David T.; Kene, Mamata V.; Vinson, David R.; Ballard, Dustin W.
Abstract: Objectives: Prior studies examining the sensitivity of cranial computed tomography (CT) for the detection of subarachnoid hemorrhage (SAH) have used the final radiology report as the reference standard. However, optimal sensitivity may have been underestimated due to misinterpretation of reportedly normal cranial CTs. This study aims to estimate the incidence of missed CT evidence of SAH among a cohort of patients with aneurysmal SAH (aSAH). Methods: We performed a retrospective chart review of emergency department (ED) encounters within an integrated health delivery system between January 2007 and June 2013 to identify patients diagnosed with aSAH. All initial noncontrast CTs from aSAH cases diagnosed by lumbar puncture (LP) and angiography following a reportedly normal noncontrast cranial CT (CT‐negative aSAH) were then reviewed in a blinded, independent fashion by two board‐certified neuroradiologists to assess for missed evidence of SAH. Reviewers rated the CT studies as having definite evidence of SAH, probable evidence of SAH, or no evidence of SAH. Control patients who underwent a negative evaluation for aSAH based on cranial CT and LP results were also included at random in the imaging review cohort. Results: A total of 452 cases of aSAH were identified; 18 (4%) were cases of CT‐negative aSAH. Of these, seven (39%) underwent cranial CT within 6 hours of headache onset, and two (11%) had their initial CTs formally interpreted by board‐certified neuroradiologists. Blinded independent CT review revealed concordant agreement for either definite or probable evidence of SAH in nine of 18 (50%) cases overall and in five of the seven (71%) CTs performed within 6 hours of headache onset. Inter‐rater agreement was 83% for definite SAH and 72% for either probable or definite SAH. Conclusions: CT evidence of SAH was frequently present but unrecognized according to the final radiology report in cases of presumed CT‐negative aSAH. This finding may help explain some of the discordance between prior studies examining the sensitivity of cranial CT for SAH.